Effect of organic chromium on the selected hematological profile of male Jawarandu goats under transportation stress - Lusia Komala Widiastuti; Anggi Derma Tungga Dewi; Muhammad Mirandy Pratama Sirat; Ratna Ermawati (Jurnal Ilmu Peternakan Terapan, 2026)
This study aimed to evaluate the effect of organic chromium supplementation on the physiological and hematological responses of male Jawarandu goats subjected to transportation stress. Nine adult male goats aged 1-2 years with an average body weight of 30.84 kg were used consisting of three treatments with three replications: T0 (no supplementation), T1 (0.5 ppm organic chromium), and T2 (1 ppm organic chromium). Transportation was carried out over a distance of 289 km with a travel time of 5 hours using an open-back pickup truck without providing feed or water. The observed parameters included total protein (refractometer), packed cell volume (PCV), basophils, eosinophils, and monocytes, measured before and after transportation. The results showed that organic chromium supplementation had no significant effect on total protein, basophils, eosinophils, and monocytes, but significantly affected PCV values. PCV values across all groups remained within the normal range for ruminants (22-38%), with a decrease in P1 indicating a role in reducing hemoconcentration, and an increase in P2 suggesting a function in maintaining red blood cell levels.